Niels Arnfred, A. Kjellberg & B. Malmgren, Stat og klasser under kapitalismen, (udvidet og omarbejdet udgave), København: Finn Blytmanns Forlag, 1981, 224 s., 105,00 kr. - Rye Olsen, Gorm (Politica, 1982)
-